Recent Advances on Phagocytic B Cells in Teleost Fish - Wu, Liting; Qin, Zhendong; Liu, Haipeng; Lin, Li; Ye, Jianmin; Li, Jun (Frontiers in Immunology, 2020)
The momentous discovery of phagocytic activity in teleost B cells has caused a dramatic paradigm shift from the belief that phagocytosis is performed mainly by professional phagocytes derived from common myeloid progenitor cells, such as macrophages/monocytes, neutrophils, and dendritic cells. Recent advances on phagocytic B cells and their microbicidal ability in teleost fish position B cells at the crossroads, bridging innate with adaptive immunity. Most importantly, an increasing body of experimental evidence demonstrates that, in both teleosts and mammals, phagocytic B cells can recognize, take up, and destroy particulate antigens and then present those processed antigens to CD4+ T cells to elicit adaptive immune responses and that the phagocytosis is mediated by pattern recognition receptors and involves multiple cytokines. Thus, current findings collectively indicate that teleost phagocytic B cells, as well as their counterpart mammalian B1-B cells, can be considered one kind of professional phagocyte. The aim of this review is to summarize recent advances regarding teleost phagocytic B cells, with a particular focus on the recognizing receptors and modulating mechanisms of phagocytic B cells and the process of antigen presentation for T-cell activation. We also attempt to provide new insights into the adaptive evolution of the teleost fish phagocytic B cell on the basis of its innate and adaptive roles.